THE EFFECT OF TWO MODES OF INSTRUCTION: MODELING VS. PRESENTATIONAL - Mujgan Buyuktas Kara; Elke Van Steendam; Gert Rijlaarsdam; Huseyin Kuru (Informascope, 2018)
We implemented an intervention of four lessons and tested the effects of two instructional modes as compared to the regular curriculum practices for completing a synthesis task at the preparatory program of a Turkish university. Participants were 48 upper-intermediate EFL learners (mean age=18) assigned to three conditions. The presentational condition received direct strategy instruction supported by mnemonics; the modeling condition observed a video of a peer doing the task using the same strategies mnemonic. In the control condition, there was no explicit reference to strategies; rather, students inferred the necessary information about writing an effective synthesis text from the instruction and the lesson materials. We hypothesized that both of the experimental conditions would have a positive effect on students' synthesis text quality and writing processes and that modeling of explicit strategy use would have an effect over and above the other conditions. Results showed that students in the modeling condition improved their source use skills significantly more than students in the presentational condition, which was maintained in the delayed posttest four weeks later. No statistically significant condition effect was observed for content and authenticity of students' texts. The modeling condition also showed and reported a more process-oriented approach to writing.